(untitled) (Journal of Sustainability, Environment and Peace, 2021)
Climate change has an impact on agriculture and subsequently food productivity and security. This study assesses adaptation and mitigation strategies to climate change by smallholder dairy farmers in the Nandi county of Kenya. Questionnaires, Focus Group Discussion (FGD) and key informant interviews were used to collect data. A Pearson’s chi-square test was used to test significant associations. Results indicate most households in study area were male headed (79.2%), with between 4 and 6 people (51.8%) and aged between 31 and 60 years (75.4%). Over 80% of households were dependent on farming as a source of income. Households depended on natural pastures on their own farms as a source of feed (76.5%) and crop residues (49.9%). Natural pastures and fodder crops were considered the most important source of feed for the cows. Fodder were planted in less than 0.5 acres of land for Napier (80.1%), Rhodes grass (57.5%), Sorghum (54%), Maize (33.4%), Kikuyu Grass (40.3%), Lucerne (59.4%) and household planting <50 fodder Trees (82.1%). Smallholder farmers conserved/preserved crop residue (88.2%), hay (39.9%) and silage (35.4%). Methods used to address negative experiences of climate change included use conserved hay/ silage (44.2%), buying of commercial feeds (40.9%), use crop residue (74.6%), moving of animals to other farms (8.8%) and selling of animals (17.4%). Measures to prevent negative effects of climate change included adoption of fodder types/varieties (54.7%) and conservation and preservation practices (70.0%). The study recommends greater attention to increase fodder crop production and conservation, support to smallholder farmers to explore new ways that would sustainably help them adapt and mitigate the effect of climate change on fodder productivity and subsequently on milk production.